Striving for crisis resolution or crisis resilience? The crisis layers and thresholds model and Information and Communication Technology‐mediated social sensing for evidence‐based crisis management and communication. Issue 1 (28th December 2020) - Gaspar, Rui; Domingos, Samuel; Brito, Duarte; Leiras, Gisela; Filipe, Jessica; Raposo, Beatriz; Telo de Arriaga, Miguel
Abstract: Do crisis evolve linearly through sequential one‐directional stages that end with their resolution? Or are crisis, a set of nonlinear events with somewhat a chaotic nature, better represented as multilayer relapse cycles, that is, a series of dynamic processes and templates that evolve at different levels of analysis and can either go forward—achievement—or go back—relapses? Moreover, should crisis always move forward to reach their resolution or should we strive to achieve social systems resilience, grounded on learning and adaptation processes, that is, moving forward and backwards, until achieving it? To argument in favor of achieving crisis resilience, we propose a theoretical model—the crisis layers and thresholds (CLT) model grounded on the following assumptions: (a) individuals' evaluations and responses should be the basis/core of crisis management and crisis communication activities; (b) different concurrent psychosocial and organizational processes occur at different levels of analysis of a crisis, from a microindividual level to a macro organization level; and (c) rather than striving for crisis resolution, we should strive for crisis resilience, preparing the social system for current and future emerging risks and crisis. To implement effective evidence‐based crisis management and crisis communication in line with such assumptions, we also propose the CLT‐ResiliScence approach, an Information and Communication Technology‐mediated crisis sensing approach. This is based on monitoring "social sensors" data, particularly from social media, as an important source of information. Examples of this will be provided based on research on the current COVID‐19 pandemic.